A coach's guide to developing exemplary leaders : making the most of the leadership challenge and the leadership practices inventory (LPI) /: making the most of the leadership challenge and the leadership practices inventory (LPI). ([2017]) - Kouzes, James M, 1945-; Posner, Barry Z; Biech, Elaine
No abstract available